The call of the wild - London, Jack, 1876-1916 (Salt Lake City, UT : Project Gutenberg, 2008)
"The Call of the Wild" by Jack London is an adventure novel published in 1903. Buck, a powerful dog living comfortably in California, is stolen and sold into service as a sled dog during the Klondike Gold Rush. Thrust into the brutal Yukon wilderness, he must fight to survive among other dogs and harsh masters. As Buck endures the unforgiving environment, he grows increasingly primitive, shedding his domesticated life and answering an ancient instinct that pulls him toward something wild and primal. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Call_of_the_Wild
Release date is 2008-07-02
Ryan, Kirstin, Linda and Rick Trapp and David Widger
Keywords: Dogs -- Fiction; Adventure stories; Nature stories; Klondike River Valley (Yukon) -- Fiction; Sled dogs -- Fiction; Pet theft -- Fiction; Feral dogs -- Fiction; Animal welfare -- Fiction